(untitled) (Challenges of the Future, 2021)
Research Question: What factors influence a successful coordination of top athletes’ dual careers? Purpose: The purpose of successfully coordinating the dual careers of top athletes is to obtain education during a sports career. The acquired education helps to increase the employability of the athlete after his / her sports career. Method: We used a quantitative method of research, descriptive analysis, linear and multiple analysis. The statistical analysis was performed with the help of the SPSS statistical programme. Results: The research found that a successful coordination of a dual career is influenced by personality factors and characteristics of the study programme. Organization: Colleges and higher education institutions should be aware that they have to adapt the studies to the athletes, as this will increase the education level of the latter. Society: Athletes will be more employable after completing their sports careers. Originality: Based on the data and findings obtained, suggestions have been made to improve the dual careers of athletes in Slovenia. Limitations / Further Research: The study was limited to only interviewing Slovenian top athletes.